(w)(w+7)=0

Simple and best practice solution for (w)(w+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w)(w+7)=0 equation:


Simplifying
(w)(w + 7) = 0

Reorder the terms:
w(7 + w) = 0
(7 * w + w * w) = 0
(7w + w2) = 0

Solving
7w + w2 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), 'w'.
w(7 + w) = 0

Subproblem 1

Set the factor 'w' equal to zero and attempt to solve: Simplifying w = 0 Solving w = 0 Move all terms containing w to the left, all other terms to the right. Simplifying w = 0

Subproblem 2

Set the factor '(7 + w)' equal to zero and attempt to solve: Simplifying 7 + w = 0 Solving 7 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + w = 0 + -7 w = 0 + -7 Combine like terms: 0 + -7 = -7 w = -7 Simplifying w = -7

Solution

w = {0, -7}

See similar equations:

| x-18sqrtx+80=0 | | I=f-1ir | | (4x^2-x)= | | (y-5)2=100 | | (x)(x+2)(2)=70 | | 6x-4=149-11x | | I=f-(IR) | | -(7xy-10)+2(5xy+7)= | | 6x-2=3x+43 | | x^2+9x+15=-4x+3 | | 2+4x-7x= | | 5X+10=3X+20 | | 10x+31=4x-11 | | )1/ | | 16-2X=8X-14 | | Y=-16x^2+200x+4 | | Y(y-10)=75 | | 5y=3.75x+25 | | 8X+15=3X+16 | | X+(X-6)*0.2= | | 10+9g=10g | | -7z-4=-8z+4 | | (x+2)*(x-2)*(x+2-3i)*(x+2+3i)=0 | | x^2/3-25=0 | | -9+4d+5=10-3d | | (5v-y+5)(6v-7)= | | 5+6r=-3r-4 | | -7w+10=-8w | | 11-4x=24-6x | | 6(x+11)=35 | | 6f+4=f+9 | | y(x)=10*1.15x |

Equations solver categories